PENERAPAN STRATEGI PEMBELAJARAN PDEODE BERBANTUAN LKPD BERBASIS AUGMENTED REALITY UNTUK MEREDUKSI MISKONSEPSI PESERTA DIDIK SMA PADA MATERI MOMENTUM DAN IMPULS - Novia Wulandari, - (2021)
In physics learning, misconceptions are one of the problems that are often experienced by students. Students often experience misconceptions about Momentum and Impulse material, which can hinder students from understanding other physics concepts. Application of Augmented Reality-Based Augmented Reality-Based PDEODE Learning Strategy Assisted Learning Strategy in physics learning is used to states its influence in reducing students' misconceptions on Momentum and Impulse material. The method used in this study is a mixed-method with an embedded mixed-method research design. The research instrument used consisted of diagnostic test questions in the format of Four-tier Momentum and Impulse (FOTMI), Augmented Reality-based worksheets, and learning implementation observation sheets. The sample in this study consisted of 30 students consisting of 7 boys and 23 girls in class XI in one of the public high schools in Central Java. The effect of the Implementing of the LKPD Augmented Reality-Based Assisted PDEODE Strategy to Reduce High School Students' Misconceptions on Momentum and Impulse was analyzed using Cohen's d effect size, the implementation of learning was shown in percentage form, and changes in conception were analyzed based on the results of the pretest and posttest. The students' misconceptions decreased from the results of the pretest (37.7%) to the results of the posttest (33.5%) of 4.2%. There was a change in the concept of Accepted Change (AC) by 32%, Not Change (NC) by 44%, and Unacceptable Change (UC) by 25%.